Three dimensional QSAR applications in pharmacology and toxicology - Doucet, Jean-Pierre (CRC Press, 2010)
"Experiencing rapid growth over the last 15 years, quantitative structure-activity relationships (QSAR) continue to evolve quickly with an explosion of new tools and techniques. These techniques now play an increasing role in drug design and chemical risk assessment. New molecular descriptors based on three-dimensional structures incorporate a range of classical approaches, including regression and PLS analysis, as well as new nonlinear approaches, such as neural networks and support vector machines. Three-Dimensional QSAR addresses the scope and limitations of different modeling techniques using case studies from pharmacology, toxicology, and ecotoxicology to demonstrate the utility of each technique"--Provided by publisher.
Keywords: QSAR (Biochemistry); Pharmacology -- Research -- Methodology.; Toxicology -- Research -- Methodology.; elektronické knihy; electronic books